Program perkongsian ilmu dan kepakaran bersama Jabatan Perangkaan Malaysia (DOSM) / Norul Fadhilah Ismail - Ismail, Norul Fadhilah (Universiti Teknologi MARA, Negeri Sembilan, 2022)
Faculty of Computer and Mathematical Sciences (FSKM) UiTM Cawangan Negeri Sembilan Kampus Kuala Pilah with the support of Department of Statistic Malaysia (DOSM), Negeri Sembilan Branch, a program on “Perkongsian Ilmu dan Kepakaran Bersama Jabatan Perangkaan Malaysia” was held on 16 September 2021 through google meet application. Two speakers from DOSM Negeri Sembilan were invited to share their experience on the importance of the census and research opportunity during the session that was attended by mostly UiTM’s lecturers from various campuses. The program was officiated by the Deputy Rector of Academic Affairs, Dr. Noorlis Ahmad. DOSM is a premier government agency entrusted with the responsibility to collect, interpret, and disseminate the latest and real-time statistics in the monitoring of national economic performance and social development. The program started with the first speaker, En. Zainuri bin Muhammad, Asisstant Director of DOSM Negeri Sembilan who has presented the impact of census data on Malaysia’s population and households on society. The census is conducted once every ten years and until now it has been carried out 6 times since the formation of Malaysia.